2003
DOI: 10.1002/lsm.10148
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of NaOCl/H2O2 irrigation and GaAlAs laser in decontamination of root canals in vitro

Abstract: The application of the diode laser might be an adjunct to conventional endodontic treatment when used in combination with a NaOCl/H(2)O(2) solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 51 publications
4
36
0
9
Order By: Relevance
“…In general, dental lasers provide greater accessibility of formerly unreachable parts of the tubular network due to their better penetration into dentinal tissues [9][10][11]. Scientific research was first conducted with the Nd:YAG [12][13][14][15] and the diode lasers [16][17][18][19], which gained widespread acceptance in the fields of laser-assisted endodontics. For both wavelengths, a high disinfecting capability was reported.…”
Section: Introductionmentioning
confidence: 99%
“…In general, dental lasers provide greater accessibility of formerly unreachable parts of the tubular network due to their better penetration into dentinal tissues [9][10][11]. Scientific research was first conducted with the Nd:YAG [12][13][14][15] and the diode lasers [16][17][18][19], which gained widespread acceptance in the fields of laser-assisted endodontics. For both wavelengths, a high disinfecting capability was reported.…”
Section: Introductionmentioning
confidence: 99%
“…52 Some studies suggested applying this technique in canals filled with irrigants such as EDTA, citric acid or NaOCl reduces the thermal side effects. 53 It should be considered that irradiation of the Nd:YAG and diode laser can create fusion and superficial re-solidification in the dentine with a clear glazed surface. 54 We should always keep in mind that it is better to move the fiber inside the canal and not to stay or touch the root canal wall for a long time to avoid producing craters with microcracks.…”
Section: Lasersmentioning
confidence: 99%
“…[63][64][65] Of the current lasers available, the CO 2 wavelength would appear least successful in effecting bacterial decontamination 66 and the effectiveness of laser use appears to depend on fl uence values and direct access. 67 In addition, some concern has been expressed that the plume produced during laser action might allow bacterial contamination to spread. 68,69 As with laser bacterial action in other clinical sites, subablative energy levels should be employed for all wavelengths.…”
Section: Bacterial Decontaminationmentioning
confidence: 99%